Continuous-variable geometric phase and its manipulation for quantum computation in a superconducting circuit - Chao Song (Nature Portfolio, 2017)
Geometric phase is of fundamental interest and has practical application in quantum computation. Here the authors observe continuous-variable geometric phase in a superconducting circuit and demonstrate a multi-qubit controlled phase gate protocol based on this geometric effect.